ASEAN banking industry performance analysis - Nindya Nuriswati Laili; Dinar Ari Prasetyo; Winarno Winarno (Diponegoro International Journal of Business, 2023)
This research focuses on the banking industry in ASEAN. The ASEAN economy is one of the economic forces that needs to be considered. This is due to the fast and significant economic growth of ASEAN even in the midst of the 2008 financial crisis. In this study, we will look at the specific influence of banks, industry, macroeconomics and Country Governance Indicators in determining banking performance in ASEAN. The research period was taken during the post-crisis period, namely 2011 to 2019. The dependent variable used was bank performance as proxied by EARTA, while the independent variables were divided into 4 main categories, specific banks, industry, macroeconomics, and Country Governance Indicators. Country Governance Indicator variable using Corruption Index. The data used is sourced from the Osiris Database for all banks in ASEAN. This study uses multiple linear regression analysis techniques. The results showed that the bank-specific variables; there are 4 variables that have a significant effect on banking performance, industry indicators have no effect on bank performance, macroeconomic specific variables have a significant effect on bank performance, while the Country Governance Indicator proxied by the Corruption Index has an effect on bank performance.